Elementary School Islamic Religious Education Teachers' Strategies in Implementing Canva-Based Learning Media in the Digital Era - Nur Widiastuti; Siti Aminah; Indah Mustikarini; Resta Novriani; Elza Agustin; Anom Galih Kusuma (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
The development of digital technology has encouraged teachers to innovate in designing engaging, interactive learning that is appropriate to the characteristics of 21st-century students. One innovation that can be implemented is the use of the Canva application as a digital learning medium. This study aims to describe the strategies of elementary school Islamic Religious Education (PAI) teachers in implementing Canva-based learning media in the digital era, identify supporting and inhibiting factors for its implementation, and analyze its impact on the learning process. This study uses a qualitative approach with descriptive methods. The research subjects included Islamic Religious Education teachers, school principals, and elementary school students. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive model that includes data reduction, data presentation, and drawing conclusions. Data validity was obtained through triangulation of sources, techniques, and time. The results of the study indicate that teachers' strategies in implementing Canva-based learning media are carried out through three main stages: planning, implementation, and evaluation of learning. In the planning stage, teachers compile teaching materials, select appropriate materials, and design Canva media by utilizing presentation features, infographics, videos, animations, and interactive quizzes. During the implementation phase, teachers integrated Canva media with discussion, question-and-answer, demonstration, and student-centered learning methods to increase student attention, motivation, participation, and understanding of Islamic Religious Education materials. The evaluation phase involved assessing attitudes, knowledge, and skills, along with reflection on the effectiveness of media use.